3 UMPSA academic staff appointed professors - Siti Sakinah, Mohtar (UMPSA, 2024)
PEKAN, 14 August 2024 - Three Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) academic staff received an appointment letter for promotion to the position of VK7 Special Grade Professor from the Vice-Chancellor, Professor Dato’ Ts. Dr. Yuserrie Zainuddin, today.